Lipocalin-2 Regulates Hippocampal Microglial Activation in Poststroke Depression - Wei, Li; Du, Yupeng; Xie, Yirui; Yu, Xiaopeng; Chen, Hui; Qiu, Yunqing (Frontiers in Aging Neuroscience, 2021)
Background and Purpose: Microglia play important role in poststroke depression (PSD), however, the exact mechanism was still unclear. The purpose of the study was to study the mechanism of microglial activation in PSD. Methods: 24 rats were randomly divided into three groups: the PSD group (n = 10), the poststroke (PS) group (n = 7), and the sham group (n = 7). Primary hippocampal microglia were isolated and cultured, and recombined LCN2 protein was used to stimulate the cultured microglia. The protein expression of Iba1, P38 MAPK and PP38 MAPK was analyzed by western blotting; the LCN2 expression was measured by RT-qPCR, the serum LCN2 level and the NO level were analyzed by ELISA. Results: Open field test scores (horizontal score, vertical score, and self-grooming score) and the serum LCN2 level were significantly decreased in the PSD group compared with the other two groups (P < 0.05). The serum LCN2 level was positively correlated with the horizontal score and negatively correlated with the self-grooming score in the open field test (P < 0.05). The relative protein level of Iba1 and the LCN2 mRNA level were significantly increased in the hippocampal region compared with other brain regions (P < 0.05), while the relative protein level of Iba1 and the LCN2 mRNA level were significantly increased in the PSD group compared with the other two groups (P < 0.05). The length, supernatant NO level, phagocytic ability and migration ability of LCN2-treated microglia were significantly increased compared with those of untreated microglia (P < 0.05). The relative protein levels of P38 MAPK and the PP38 MAPK significantly increased in hippocampal region in the PSD group and LCN2-treated hippocampal microglia (P < 0.05). Conclusion: Hippocampal microglia are activated during PSD; LCN2 may regulate hippocampal microglial activation by the P38 MAPK pathway in the process of PSD.